Analysis of The Need for Using Geospatial Technology in Developing Electronic Student Worksheet - Nabil, Ziyad Fadhlan; Efendi, Ridwan; Novia, Hera (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This study aims to determine the need to develop student worksheets based on Geospatial Technology as a learning resource for physics students in high school. This study focuses on quantitative research using questionnaires that are analyzed using descriptive statistics. This study involved 23 respondents spread across several schools in Padang, West Sumatra and 32 students in one of the high schools in Padang City, West Sumatra. The instrument in this study uses a needs questionnaire with several statements addressed to teachers and students. Based on the teacher needs questionnaire, as many as 60.9% of the 23 teachers do not know this technology, so only 39.1% know it but only 8.7% apply it in learning. The results of the needs questionnaire analysis show that student worksheets developed with Geospatial Technology, especially on the topic of renewable energy sources, are needed and are expected to help students achieve their desired learning goals. Based on this, the use of technology as a learning resource is urgently needed by students, so it is necessary to conduct a needs analysis in developing student worksheets based on Geospatial Technology.